Study of [ypsilon] production and cold nuclear matter effects in pPb collisions at √sNN=5 TeV - Aaij, Roel; Adeva, B.; Adinolfi, M.; Bachmann, Sebastian; Bien, Alexander; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; et al. (Journal of high energy physics, 2014)
Production of Υ mesons in proton-lead collisions at a nucleon-nucleon centre-of-mass energy √sNN = 5 TeV is studied with the LHCb detector. The analysis is based on a data sample corresponding to an integrated luminosity of 1.6 nb−1. The Υ mesons of transverse momenta up to 15 GeV/c are reconstructed in the dimuon decay mode. The rapidity coverage in the centre-of-mass system is 1.5 < y < 4.0 (forward region) and −5.0 < y < −2.5 (backward region). The forward-backward production ratio and the nuclear modification factor for Υ(1S) mesons are determined. The data are compatible with the predictions for a suppression of Υ(1S) production with respect to proton-proton collisions in the forward region, and an enhancement in the backward region. The suppression is found to be smaller than in the case of prompt J/ψ mesons.
*The LHCb collaboration: R. Aaij, S. Bachmann, A. Bien, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, P. Seyfert, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelelov [und sehr viele weitere Personen]
Im Titel ist "Ypsilon" als griechischer Buchstabe dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel ist der Buchstabe s hochgestellt